Hip Rotator Strength in Healthy Young Adults Measured in Hip Flexion and Extension by Using a Hand‐held Dynamometer. Issue 12 (17th June 2014) - Bloom, Nancy; Cornbleet, Suzanne L.
Abstract : Objective: To investigate the effect of hip joint position on hip rotator muscle strength of healthy young adults by using a hand‐held dynamometer. Design: A cross‐sectional cohort study. Setting: A university medical center. Participants: Thirty‐four healthy (19 women, 15 men; mean [standard deviation] age, 25 ± 2.3 years) participated in this study. Methods: A hand‐held dynamometer was used to measure the strength of hip internal rotators and external rotators in 2 positions: hip flexion in sitting and hip extension in supine. The hip was tested in a neutral position with respect to rotation, abduction, and adduction. Isometric force in pounds was measured as the subject pushed against the device. Main Outcome Measurements: For each subject, hip rotator muscle strength measurements were taken during a single session. Hypotheses were developed before data collection. Results: Hip internal rotators were significantly stronger in hip flexion compared with hip extension ( P < .01). There was no significant difference found in the hip external rotators between the 2 positions. Conclusions: Hip internal rotators and external rotators behave differently when comparing strength measurements between the positions of hip flexion and hip extension. A hand‐held dynamometer provided an objective measurement of strength that was clinically feasible to use. Both muscle length and moment arms influence force production of the hip rotators as the hip position changes. Understanding these relationships may help clinicians interpret strength findings and direct intervention toward strengthening the appropriate muscles by using the most advantageous position.